Motivation of Farmer Group Members in Rice Cultivation Using Technical Irrigation Methods in Candibinangun Village, Yogyakarta, Indonesia - Rozaki Zuhud; Romadhoni Muhammad; Rahmawati Nur; Wulandari Retno; Ardila Riska Aula; Fathurrohman Yusuf Enril (E3S Web of Conferences)
Farmers in Candibinangun Village use technical irrigation in rice cultivation because the amount of water is sufficient and for the costs of rice cultivation cheaper than other commodities. This research aims to determine the motivation and factors related to rice farmers in cultivating rice using technical irrigation in Candibinangun Village, Yogyakarta. This research uses quantitative methods using purposive sampling. The technique for collecting respondents was carried out deliberately using certain methods on a sample of 30 farmers. The results of this research are the need for existence with a score of 2.94 in the high category, the need for relationships with a score of 3.06 in the High category and the need for growth 2.86 in the high category. So, the ERG motivation of farmers in maintaining rice farming received a score of 2.94 in the high category. In this study, internal factors were significant and insignificant and external factors were significant and insignificant.